184k views
25 votes
X - y = -2 7x + 2y = -5

Élimination method

X - y = -2 7x + 2y = -5 Élimination method-example-1
User Jonatzin
by
4.9k points

1 Answer

2 votes

Answer:

x = -1, y = 1

Explanation:

Multiply the top equation by 2:


2x - 2y = - 4

Leaving the bottom equation unchanged, add the two resulting equations to eliminate y, obtaining:


9x = - 9

Solve this for x, and then substitute this value of x into the bottom equation. Finally, solve for y.


x = - 1


7( - 1) + 2y = - 5


- 7 + 2y = - 5


2y = 2


y = 1

User Cabita
by
4.9k points